Effects of new residential developments on local healthcare demand and workforce: Evidence from primary and acute public hospital care in Ireland - Harry Humes; Michelle Barrett; Brendan Walsh (The Economic and Social Research Institute (ESRI), 2024)
Housing and health are critical issues for policymakers and the public. Secure and affordable housing, along with quick access to required health and social care, are considered essential services for the public and are key targets for planners. In Ireland, as in many countries, the need to improve accessibility to housing and health is already understood, and support for both housing and health are fundamental parts of the social welfare system. There is also a significant synergy between the areas of housing and health. A well-established body of evidence demonstrates the link between housing conditions and health outcomes. Poor housing and insecure tenure can adversely affect health and wellbeing, and the World Health Organization (WHO) cites housing, basic amenities and the environment as primary social determinants of health. Location of housing and healthcare are also highly correlated. In Ireland, disparities in access to health and social care services are evident across different geographic areas and demographic groups. Regions that experienced the largest population growth in recent decades consistently have the most limited healthcare resources. The establishment of a population-based resource allocation (PBRA) system within the public health sector may help reduce some of these supply inequalities. While against the backdrop of ongoing population increases and demographic shifts, policies aimed at a proportional increase in healthcare supply are crucial. This necessitates that healthcare and housing policymakers align their strategies and where possible integrate planning policies. Coordinated planning is vital to ensure that housing developments are matched with sufficient healthcare services, creating sustainable communities where residents have both secure housing and dependable healthcare.
Keywords: 330; Gesundheitsversorgung; Krankenhaus; Medizinische Behandlung; Wohnungsmarkt; Bevölkerungsentwicklung; Wohnungspolitik; Gesundheitspolitik; Irland